The Perceptions to Climate Change among Rural Farming Households in the Niger Delta Area, Nigeria - P. O, Emaziye (Asian Journal of Agriculture and Rural Development, 2013)
The study focused on the perceptions to climate change among rural farming households in the Niger Delta Area, Nigeria. The basic objective was to determine the rural farming household’s perception to climate change in the Area and the specific objective was to determine the direction of change of the climate change indicators (whether increasing, decreasing or constant). Multistage sampling procedure was sampled 739 rural farming households (respondents) for the study. Data were analyzed using descriptive statistic. Socio – economic profile of the respondents indicated that 37.69% of rural farming households falls between the age bracket of 47 to 51 years and majority (60.0%) having educational qualification below secondary school level. The study also reveals 76% had no extension contact during the farming season and 78.6% of respondents are not aware of the phenomenon of climate change. The study noticed an increasing change in the climate change indicators except longer raining season that is decreasing in the Area. The perception to the cause of climate indicators was mostly attributed to natural occurrence by God/gods (67.7%). Awareness campaign on climate change is recommended in the rural areas for climate change information.